Smoking influence in Takotsubo syndrome: insights from an international cohort - Núñez-Gil, Iván J.; Santoro, Francesco; Vazirani, Ravi; Novo, Giuseppina; Blanco-Ponce, Emilia; Arcari, Luca; Uribarri, Aitor; Cacciotti, Luca; Guerra, Federico; Salamanca, Jorge; Musumeci, Beatrice; Vedia, Oscar; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims: To assess the influence of tobacco on acute and long-term outcomes in Takotsubo syndrome (TTS). Methods: Patients with TTS from the international multicenter German Italian Spanish Takotsubo registry (GEIST) were analyzed. Comparisons between groups were performed within the overall cohort, and an adjusted analysis with 1:1 propensity score matching was conducted. Results: Out of 3,152 patients with TTS, 534 (17%) were current smokers. Smoker TTS patients were younger (63 ± 11 vs. 72 ± 11 years, p 0.001), less frequently women (78% vs. 90%, p 0.001), and had a lower prevalence of hypertension (59% vs. 69%, p 0.01) and diabetes mellitus (16% vs. 20%, p = 0.04), but had a higher prevalence of pulmonary (21% vs. 15%, p 0.01) and/or psychiatric diseases (17% vs. 12%, p 0.01). On multivariable analysis, age less than 65 years [OR 3.85, 95% CI (2.86-5)], male gender [OR 2.52, 95% CI (1.75-3.64)], history of pulmonary disease [OR 2.56, 95% CI (1.81-3.61)], coronary artery disease [OR 2.35, 95% CI (1.60-3.46)], and non-apical ballooning form [OR 1.47, 95% CI (1.02-2.13)] were associated with smoking status. Propensity score matching (PSM) 1:1 yielded 329 patients from each group. Smokers had a similar rate of in-hospital complications but longer in-hospital stays (10 vs. 9 days, p = 0.01). During long-term follow-up, there were no differences in mortality rates between smokers and non-smokers (5.6% vs. 6.9% yearly in the overall, p = 0.02, and 6.6%, vs. 7.2% yearly in the matched cohort, p = 0.97). Conclusions: Our findings suggest that smoking may influence the clinical presentation and course of TTS with longer in-hospital stays, but does not independently impact mortality.